Passeggiando per la Federico II... tra qualche anno (FedOA - Federico II University Press, 2025)
This small volume celebrates the 800th anniversary of the “Federico II” by summarizing through themes and images a long design experimentation on the architectural heritage of the University that sees the Architecture students as protagonists in the dual role of designers and users. As the title itself tells, “Walking through the Federico II ... in a few years” prefigures, in the wake of the evocative ‘knowledge walk’ curated by Alessandro Castagnaro (FedOAPress 2019, 2024), itineraries between new relational spaces of the Federico II locations, visionary scenarios that reveal aspirations and ideas for a university life intertwined with the cultural everyday life of the city and with the environmental myths of the Greek polis latent in the Neapolitan geomorphological matrix. This significant broadening of the gaze is the prospective horizon outlined by the “Strategic Plan of the University” drawn up in July 2021, in the aftermath of the pandemic phase. The huge and prestigious architectural heritage of the Federico II pervades all the urban parts of the Neapolitan territory. In the suburbs as in the center, its physical and cultural presence is manifested through a heterogeneous multiplicity of typological solutions that include both the reuse of convents and civil buildings and university complexes built from scratch in contexts with strong landscape values. The different interpretative angles of the disciplinary sectors involved in the Design Laboratories reveal its great potential as structuring poles of urban centrality in the four large geographical-urban contexts directly projected onto the Neapolitan metropolitan dimension.